Blade runner [videorecording (Blu-Ray)] - Hannah, Daryl; Turkel, Joe, 1927-; Cassidy, Joanna, 1945-; Walsh, M. Emmet, 1935-; James, Brion, 1945-1999; Sanderson, William, 1944-; Deeley, Michael; Fancher, Hampton; Peoples, David Webb; Perenchio, Jerry; Yorkin, Bud, 1926-2015; Scott, Ridley; et al. (Distributed by Warner Home Video, 2010)
Los Angeles, 2019: Rick Deckard of the LAPD's Blade Runner unit prowls the steel & microchip jungle of the 21st century. His job is to track down and eliminate genetically engineered humanoids known as 'replicants.' Replicants were declared illegal after a bloody mutiny on an Off-World Colony, and are to be terminated upon detection. He wants to get out of the force, but is drawn back in when 6 "skin jobs," the slang for replicants, hijack a ship back to Earth. The city that Deckard must search for his prey is a huge, sprawling, bleak vision of the future.